ANALISIS MUTU BETON BERBAHAN FABA (FLY ASH BOTTOM ASH) SEBAGAI PENGGANTI AGREGAT HALUS DENGAN MENGACU PROPORSI CAMPURAN PADA ANALISA HARGA SATUAN PEKERJA - Samawi, Nur Aini Widya; Saputro, Yayan Adi; Hidayati, Nor (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2024)
In this research, the author used FABA (Fly Ash Bottom Ash) waste as an alternative to fine aggregate. This research can determine the physical properties of faba aggregate with the results of sieve analysis testing of faba aggregate which has a fineness modulus value of 2.34 which is included in the medium fine aggregate type. Testing for water content in faba fine aggregate in SSD conditions was 3.09%. Faba fine aggregate sludge content is 0%. Testing the organic substances on the faba fine aggregate showed that the NaOH color was reddish brown, because it needed to be washed first before being used as a concrete mixture. The face dry specific gravity of faba fine aggregate is 2.2 gr/cm2. Therefore, faba aggregate can be used as a substitute for sand because it has physical properties that meet the requirements as fine aggregate. Results The final compressive strength of faba concrete and normal concrete as a control at the age of 7 days and 28 days has reached the planned quality, but the compressive strength at normal concrete (control) is higher than faba concrete. With the results of the standard deviation values ​​at 7 days and 28 days, it is included in perfect workmanship condition because it has a standard deviation value of less than 3 MPa. The results of the concrete flexural strength test were only normal K300 concrete with a flexural strength of 4.60 MPa, which complies with SNI 2847:2013, namely producing a minimum flexural strength of fs = 4.4 MPa. Normal concrete has a much higher flexural strength than faba concrete, and the higher the quality of the planned concrete, the greater the resulting flexural strength of the concrete.